The impact of Non-Performing Loans on the Banks’ Profitability - Diakomihalis, Mihail; Economakou, Sofia (International Conference on Business and Economics - Hellenic Open University, 2023)
The global financial system after and during the financial crisis had to face the major issue which has extremely influence their profitability: The Non-Performing Loans portfolio (NPLs). The present study aims to reveal the interrelation and the possible impact of the NPLs to the profitability indicators of the Greek banks and specifically how they affect the profitability of the banks. The empirical investigation of included a comparative study of Financial ratios of certain Greek banks were calculated in order to reveal the impact of Non-Performing loans to their profitability for the year 2017. Interest income on loans is positive for all Banks but with a wide variation, while Interest-Expenses show an asymmetric distribution. Overdue loans for more than 90 days show uniformity with the exception of Piraeus Bank which shows an extreme price. The correlation between ROA and ROE with loans is not statistically significant. The effect on the Equity of loans in all forms except regulated is considered statistically significant. The negative effect of NPLs for more than 90 days on Net Profit before Tax is considered statistically significant. JEL Classifications: G210, D140, G300, O160 Key words: Non- Performing loans, Greek Banks, Profitability, Credit risk, Legal frame of NPLs